The Relationship Between Internet Addiction and Sleep Quality Among Human Sciences Undergraduates During The Covid-19 Pandemic - Syeha Nafisah Busubul; Shukran Abdul Rahman (Psycho Idea, 2021)
A cross-sectional study was conducted to investigate the relationship between internet addiction and sleep quality among Human Sciences undergraduates during the COVID-19 pandemic in Malaysia. A group of 36 male (M=36) and 132 female (F=132) undergraduates, age ranged between 17-29 participated in the study. The Internet Addiction Test (IAT) was used to measure the level of internet addiction while the Pittsburgh Sleep Quality Index (PSQI) was used to measure sleep quality. Using Spearman’s rho Correlation Coefficient to analyse the relationship, the study found a statistically significant positive correlation between internet addiction and sleep quality (rs(166)=.190, p=.007). This indicated that higher level of internet addiction was associated with progressively worse sleep quality. The findings could be useful for psychologists, educational counselors, government, researchers, and students in designing interventions to help students using the internet without the risk of addiction and improve their quality of sleep. Implications, limitations of the study, and suggestions for future research were discussed.